A Discourse Analysis on The Theoretical Value of Illichian Discourse - Çağlayandereli, Mustafa; Tamaç, Sibel (Journal of Applied And Theoretical Social Sciences, 2023)
In this article, Ivan Illich's corpus has been examined in accordance with the critical discourse analysis technique and it has been found that his systematic criticisms of modern social institutions constitute a unique sociological discourse. The main purpose of this analysis is to propose Illich's discourse among contemporary sociological theories through a broader study. The special importance of such a proposal is that it will contribute relatively to the science of sociology, which has been criticized for "not developing theory". The main data source of this analysis is 12 books written by Ivan Illich. The context of this analysis is Ivan Illich's biography and intellectual interactions. The theoretical framework of the study consists of the concepts and propositions developed by the Frankfurt Critical School and Ivan Illich for the analysis of modern society. Of these, 12 unique concepts belonging to Ivan Illich have been identified and defined. Additionally, Ivan Illich's language and rhetoric were examined and found to be compatible with his discourse. As a result of all this review, it has been found that Ivan Illich's discourse, which focuses on the criticism of modern social institutions, has the characteristics that a sociological theory should have.